Analisis Kesiapan Penerapan Rekam Medis Elektronik dengan Metode DOQ-IT di Puskesmas Kendit Situbondo - Nabila Agustina; Maya Weka Santi; Gamasiano Alfiansyah; Sabran Sabran (Puslitbang Sinergis Asa Professional, 2026)
Kendit Public Health Center currently uses paper-based medical records and has only recently begun implementing electronic medical records (EMR) in several service areas. However, this implementation faces numerous challenges, including data duplication, file damage, and the accumulation of 9,424 physical records. This situation highlights the importance of accelerating the comprehensive implementation of Electronic Medical Records (EMR) to enhance the efficiency of patient data management. This study aims to analyze the readiness for EMR implementation using the DOQ-IT method. This descriptive research involved 53 respondents, with data collected through questionnaires. The results showed that organizational alignment readiness was in the “very ready” category with a score of 31.72 out of a maximum score range of 45. The subvariables included culture (mean: 3.56), leadership (mean: 3.53), and strategy (mean: 3.47) on a 1 – 4 scale. Meanwhile, organizational capacity readiness was in the “moderately ready” category with a score of 59.77 out of a maximum score range of 100. The subvariables included information management (mean: 3.11), clinical and administrative staff (mean: 3.07), training (mean: 3.42), workflow process (mean: 2.92), accountability (mean: 2.75), budgeting (mean: 3.12), patient involvement (mean: 2.58), IT management (mean: 3.06), and IT infrastructure (mean: 2.80) on a 1 – 4 scale. Improvements are needed in organizational capacity, particularly in patient involvement, accountability, and IT infrastructure.